Xanthogranulomatous Pyelonephritis with Pyonephrosis and Renal Abscess in a Young Adult: A Consequence of Neglected Urinary Tract Infection Leading to Nephrectomy - Ali Ariyono; Maria F Pudjohartono; Thomas Rikl; Hanggoro Tri Rinonce; Hadi Irawiraman; Yulita Pundewi Setyorini; Daisy Tumedia (Acta Medica Indonesiana)
Xanthogranulomatous pyelonephritis (XGP) is a rare form of chronic pyelonephritis, which is challenging to diagnose because its clinical presentation mimics other entities and is commonly associated with a history of urinary tract obstruction. We report a case of XGP in a young adult without nephrolithiasis and urinary tract obstruction. A 23-year-old woman presented with intermittent abdominal pain in the right upper quadrant persisting for the last ten months. The pain was dull, poorly localized, and started spreading to the right back, right shoulder, and right thigh in the last three months. Other complaints included fever, chills, pain during urination, and nausea. The patient had a history of infrequent urination, recurrent urinary tract infections (UTIs), and a low fluid intake. A physical examination revealed that the patient had right upper quadrant abdominal tenderness and right costovertebral angle tenderness. Laboratory findings showed leukocytosis and neutrophilia. The radiological examination revealed a round mass in the superior pole of the right kidney with mixed cystic and solid components, and a well-defined margin. It further enlarged from 4.5 cm to 10.6 cm in diameter in three months. The urologist performed a total right nephrectomy. The histopathological examination showed XGP with renal abscess. Proteus mirabilis was identified from the pus specimen culture. XGP should be considered in the diagnosis of patients having chronic UTI presented with or without the findings of urinary tract obstruction.